Potential of Human Norovirus Surrogates and Salmonella enterica Contamination of Pre-harvest Basil (Ocimum basilicum) via Leaf Surface and Plant Substrate - Li, Dan; Uyttendaele, Mieke (Frontiers in Microbiology, 2018)
Fresh produce has been identified as an important vehicle for foodborne pathogen transmission and fresh culinary herbs have occasionally been associated with human pathogens and illness. In this study, the fate of human NoV surrogates (murine norovirus 1 [MNV-1] and Tulane virus [TV]) and three strains of Salmonella enterica on pre-harvest basil (Ocimum basilicum) was investigated. The persistence after contamination via either leaf surface or plant substrate was tested respectively. After 3 days, both MNV-1 and TV on pre-harvest leaves were at non-detectable levels (>5.5-log reduction for MNV-1 and >3.3-log reduction for TV). The three Salmonella strains showed consistent reductions of 3 to 4-log. At day 6 and 9, all the tested samples showed low levels of infectivity which were close or below the detection limits (1.7-log PFU/sample leaf for MNV-1 and TV, 0.7-log CFU/sample leaf for Salmonella) except for S. Thompson FMFP 899, one out of three samples showed to maintain present at exceptional high levels (day 6: 5.5-log CFU/sample leaf; day 9: 6.7-log CFU/sample leaf). Possibilities of microbial internalization into the edible parts of basil via the roots was demonstrated with both MNV-1 and S. enterica Thompson FMFP 899. The infectivity of internalized MNV-1 and S. enterica both decreased to non-detectable levels within 9 days after inoculation. Moreover, it should be noticed that very high microbial inoculation was used in the experimental set-up (8.46-log PFU/ml of MNV-1, 8.60-log CFU/ml of S. enterica), which is abnormal in the real-life expected contamination scenario. Within the tested scenarios in this study, S. enterica contaminated on the adaxial leaf surface of basil plants while in growth, and remained/reached a high population of over 6-log CFU/sample leaf after 9 days in one out of three samples, thus showed the highest potential for causing foodborne infection.